PENINGKATAN KUALITAS KEMENYAN DENGAN MENGGUNAKAN PELARUT ORGANIK - Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1995)
This experiment is intended to improve the quality of the several types of benzoin by using an aceton solvent. The benzoin consisted of four samples with decreasing order of  quality: "mata kasar",   "mata halus", "jurur" and "abu". All of  these  samples  were obtained from Tarutung North Sumatera. A general linear models procedure in the SAS computer package was employed to analyze the effect of the acetone solvent extraction and benzoin quality on physico chemical properties of benzoin.Results showed that the acetone solvent extraction. type of benzoin and the interaction of both gave a highly significant effect on moisture contens. Softening points, number of saponifications, solubility in ethanol. ash contents.  benzoin acid, calculated as cinnamic acids; except the effect of interaction  on softening  points. Furthermore,  the LSD analysis between means indicated that there were significant  differences  on physico  - chemical properties  among the type of benzoin, exclude the means value of solubility in alcohol between "mata kasar" and "mata halus".  and between "jurur" and "abu". There was also no significant difference on an ash content means value between "mata kasar" and "mata halus".  This aceton solvent extraction increased tire quality of "mata kasar" and "mata halus" benzoin to meet the first and tire second quality requirement of the Indonesian National Standard.  respectively. However,  the softening point of jurur benzoin did not meet second quality requirement of this standard. Overall,  the aceton solvent extraction can improve the quality of benzoin as indicated by an increase  in benzoin value, calculated as cinnamic acids, and a decrease in dirt content value.